2009
DOI: 10.1016/j.thromres.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis infection and prothrombotic effects in human aortic smooth muscle cells

Abstract: Introduction-Accumulating evidence has demonstrated an association between periodontal infectious agents, such as Porphyromonas gingivalis, and vascular disease. Tissue factor (TF) and its specific tissue factor pathway inhibitor (TFPI) are produced by vascular smooth cells and are important regulators of the coagulation cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…This lesion may be the end result of a chronic insidious inflammatory process initiated by Pg infection [41,60]. Pg has been shown to activate arterial endothelial cells, increasing the expression of cell adhesion molecules that attract leukocytes and enhanced pro-coagulant responses in these cells [41,61]. Arteritis found in acutely infected animals as well as TNF expressing macrophages found in chronically infected animals are indicative of mesometrial vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This lesion may be the end result of a chronic insidious inflammatory process initiated by Pg infection [41,60]. Pg has been shown to activate arterial endothelial cells, increasing the expression of cell adhesion molecules that attract leukocytes and enhanced pro-coagulant responses in these cells [41,61]. Arteritis found in acutely infected animals as well as TNF expressing macrophages found in chronically infected animals are indicative of mesometrial vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are rooted in literature demonstrating linkages between infection, chronic inflammation and atherosclerosis [8,5557]. Although the mechanism underlying the connection between atherosclerosis and periodontal disease remains somewhat obscure, oral pathogens have been shown to activate the major cell types involved in atheroma development, including endothelial cells [58–62], smooth muscle cells [63,64], monocytes [6568] and platelets [69,70]. …”
Section: Periodontal Disease Atherosclerosis and Cardiovascular Diseasementioning
confidence: 99%
“…P. gingivalis infection activates host cells via TLR2 and TLR4 -mediated cell signaling (Hajishengallis et al, 2006), (Hayashi et al, 2010). The smooth muscle cells (SMC) were found to respond to bacteria in a prothrombotic or in a proliferative manner (Roth et al, 2009), (Wada and Kamisaki, 2010). In the latter communication, it was shown that SMC proliferation in distal aorta aneurysms was associated with presence of P. gingivalis in the dental plaque of the patients.…”
Section: Proatherogenic Consequences Of Bacterial Presence In Vasculamentioning
confidence: 92%
“…Live invasive P. gingivalis, but not heat-killed or non-invasive mutant specifically suppressed tissue factor pathway inhibitor (TFPI) produced by vascular cells. The results suggested a procoagulant response of the host cells to bacteria (Roth et al, 2009).Plaque rupture, leading to exposure of the prothrombotic plaque core to the circulation and thrombus formation can be attributed to bacteria-dependent release of metalloproteinases (MMPs) with concomitant suppression of the MMP antagonist, tissue inhibitor of MMPs (TIMP) (Sato et al, 2009), (Guan et al, 2009). Animal models furnish a useful research tool and are indispensable in testing hypotheses at a pre-clinical stage (Graves et al, 2008).…”
Section: Proatherogenic Consequences Of Bacterial Presence In Vasculamentioning
confidence: 99%